Il potere e le libertà. Il percorso di un costituzionalista Atti del Convegno per il centenario della nascita di Paolo Barile - Stefano Merlini (Atti, 2019)
This volume is a collection of the reports and writings presented during the Conference held in Florence on the 1st December 2017, organized by the "Piero Calamandrei - Paolo Barile" centre for political and constitutional studies on the centennial of Paolo Barile's birth. The collected speeches reconstruct Paolo Barile's life and thoughts, from his cultural and scientific training during his youth to joining the judiciary, becoming a member of the Italian Action Party, the Resistance, then his meeting with Piero Calamandrei, his studies and the career as university professor. The professorship was never really separated from his strong civil and cultural commitment, from the exercise of his beloved lawyer profession and from a constant political commitment which led him to become a Minister during Ciampi's Government in 1993.